Supply project planning in a networked environment. (1st January 2001) - Tanskanen, Kari
Multi-organisational technological projects are commonplace today. The means of cooperation between organisations varies. A common basis for interorganisational project planning is needed. Simo-2, developed at the Prosit 9 Virtual delivery project, is just such a tool. It is a distributed business simulation environment, which uses a product model-based approach for power plant deliveries. It brings a unified and concrete representation of the intended project structure. This paper concentrates on the project model structure of Simo-2 and describes how software application can be used in preliminary project planning.